Commodity Taxes, Wage Determination and Profits - Sophia Delipalla; Peter Sanfey (University of Kent, Department of Economics, 1998)
We examine the effects of two different types of commodity taxation, specific and ad valorem, on wages and profits. We analyze two models of wage determination, one with efficiency wage setting and one with bargaining between a union and a firm. In the former, a (locally) revenue-neutral shift from specific to ad valorem taxation leads to an increase in both employment and wages, and a reduction in profitability. In the bargaining case however, the effect on wages and profits may be reversed: predominantly ad valorem taxation raises employment but lowers wages, and under certain circumstances, the net effect can lead to an increase in profits.
Keywords: H2; H32; J41; J5; 330; Commodity taxation; specific tax; ad valorem tax; efficiency wage; bargaining; Verbrauchsteuer; Spezielle Verbrauchsteuer; Effizienzlohn; Verhandlungstheorie des Lohnes; Theorie